Diarrhoea prevalence in children under five years of age in rural Burundi: an assessment of social and behavioural factors at the household level - Katharina Diouf; Patrik Tabatabai; Jochen Rudolph; Michael Marx (Taylor & Francis Group, 2014)
Background: Diarrhoea is the second leading cause of child mortality worldwide. Low- and middle-income countries are particularly burdened with this both preventable and treatable condition. Targeted interventions include the provision of safe water, the use of sanitation facilities and hygiene education, but are implemented with varying local success. Objective: To determine the prevalence of and factors associated with diarrhoea in children under five years of age in rural Burundi. Design: A cross-sectional survey was conducted among 551 rural households in northwestern Burundi. Areas of inquiry included 1) socio-demographic information, 2) diarrhoea period prevalence and treatment, 3) behaviour and knowledge, 4) socio-economic indicators, 5) access to water and water chain as well as 6) sanitation and personal/children's hygiene. Results: A total of 903 children were enrolled. The overall diarrhoea prevalence was 32.6%. Forty-six per cent (n=255) of households collected drinking water from improved water sources and only 3% (n=17) had access to improved sanitation. We found a lower prevalence of diarrhoea in children whose primary caretakers received hygiene education (17.9%), boiled water prior to its utilisation (19.4%) and were aged 40 or older (17.9%). Diarrhoea was associated with factors such as the mother's age being less than 25 and the conviction that diarrhoea could not be prevented. No gender differences were detected regarding diarrhoea prevalence or the caretaker's decision to treat. Conclusions: Diarrhoea prevalence can be reduced through hygiene education and point-of use household water treatment such as boiling. In order to maximise the impact on children's health in the given rural setting, future interventions must assure systematic and regular hygiene education at the household and community level.